Alteraciones musculoesqueléticas del pulgar por uso constante de dispositivos móviles - Cuadrado Silva, Luis Miguel (2023)
ABSTRACT: The present research is a bibliographic review entitled "Musculoskeletal alterations of thethumb due to the constant use of mobile devices," belonging to a line of health research in physical rehabilitation. Scientific articles were collected through scientific databases such as PubMed and Google Scholar. Digital files having information on musculoskeletaldisorders of the thumb were studied, focused on figuring out the effects of the main physiotherapeutic techniques and protocols applied on pain, joint range, and disability in the main neuromusculoskeletal alterations of the thumb. Articles published in English and Spanish between 2012 and 2023 were selected. Neuromusculoskeletal disease is an inflammatory or degenerative condition of muscles, tendons, joints, ligaments, andnerves. It usually occurs in the joints of the wrist and hand. The most common diagnosesare Quervain's tenosynovitis, carpal tunnel, and arthritis of the hand and spring finger, where the main symptoms are pain related to inflammation, loss of strength, and regionalreduction or disability of the affected area. The treatment includes conservative, pharmacological, and physiotherapeutic measures such as Kinesio taping, acupuncture, neurodynamic techniques, and orthoses, which counteract the symptoms by 90%. The method used was documentary, with inductive and descriptive methods. After an analysisof experimental scientific articles, it has been shown that different techniques for treatingTMPs positively affect patients suffering from these conditions. Keywords: musculoskeletal disorders, thumb, pain, disability. Firmado electrónicamente por: MARIA FERNANDAPONCE MARCILLO Reviewed by: Mgs. Maria Fernanda Ponce ENGLISH PROFESSOR C.C. 0603818188